Internal Carotid Artery Blister Aneurysm: Review of Endovascular Techniques - Gupta, Vipul; Londhe, Shrikant; Parthasarathy, Rajsrinivas (Journal of Clinical Interventional Radiology ISVIR, 2021)
Cerebral blister aneurysms are very difficult vascular lesions in terms of accurate diagnosis as well as proper management strategy for vascular neurosurgeons and neurointerventionists. Histopathological analysis has revealed their nature to be more akin to pseudoaneurysms in comparison to the typical berry aneurysms. This explains their fragile nature, with high probability of rerupture and regrowth during the follow-up if not addressed properly. Even though surgical approaches have evolved over the years to minimize intraprocedural rupture and recurrence, they still have relatively high morbidity as well as mortality in comparison to endovascular treatment. Over the last few years, endovascular treatment has evolved significantly, with introduction of new devices and techniques. Focus of the endovascular management has shifted from the deconstructive techniques to reconstructive ones with parent artery preservation. Recent introduction of flow diverter technology has enabled neurointerventionists to manage these difficult lesions with more confidence in terms of avoiding rerupture and recurrence. Flow diverter (FD) use in blister aneurysm resulted in high-technical success, complete aneurysm occlusion, and less complications in comparison to other reconstructive techniques like simple coiling, stent assisted coiling, and overlapping/monotherapy stent placement. Few debatable issues like use of dual antiplatelets in the setting of acute subarachnoid hemorrhage (SAH), timing of drugs in relation to procedures, single/overlapping devices, and concerns during cerebral vasospasm phase need further detailed analysis and standardized protocols. In this article, we have done a review of different endovascular treatment options in the management of internal carotid artery blister aneurysms with special focus on FD and issues related to it.
Keywords: blister aneurysms; endovascular management; flow diverter